2002
DOI: 10.1037/0096-1523.28.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Baseball outfielders maintain a linear optical trajectory when tracking uncatchable fly balls.

Abstract: The authors investigated whether behavior of fielders pursuing uncatchable fly balls supported either (a) maintenance of a linear optical trajectory (LOT) with monotonic increases in optical ball height or (b) maintenance of optical acceleration cancellation (OAC) with simultaneous lateral alignment with the ball. Past work supports usage of both LOT and OAC strategies in the pursuit of catchable balls headed to the side. When balls are uncatchable, fielders must choose either optical linearity or alignment at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 83 publications
3
79
0
Order By: Relevance
“…It differs remarkably from what sportsmen, such as baseball outfielders, do in comparable three-dimensional interceptive tasks in which the direction of target motion is not restricted within a narrow range (e.g. Chapman, 1968;McBeath et al, 1995;Regan, 1997;van der Camp et al, 1997;Shaffer and S. Wöhl and S. Schuster How to set take-off speed? What could be an advantage for the fish to adjust take-off speed to distance rather than simply heading off at maximum speed?…”
Section: Discussionmentioning
confidence: 99%
“…It differs remarkably from what sportsmen, such as baseball outfielders, do in comparable three-dimensional interceptive tasks in which the direction of target motion is not restricted within a narrow range (e.g. Chapman, 1968;McBeath et al, 1995;Regan, 1997;van der Camp et al, 1997;Shaffer and S. Wöhl and S. Schuster How to set take-off speed? What could be an advantage for the fish to adjust take-off speed to distance rather than simply heading off at maximum speed?…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the nonsegmented version of LOT could not explain the perturbed trajectories, while OAC (and thus, GOAC) could (Fink et al, 2009). However, researchers have pointed to several aspects of this study that seem to weaken these conclusions (Shaffer & McBeath, 2002;Shaffer et al, 2008;Shaffer, McBeath, Roy, & Krauchunas, 2003), not the least of which being that the version of LOT that failed was based on tangents, rather than the optical angles that are the actual basis of the LOT strategy (McBeath et al, 1996).…”
Section: Research Using Midflight Disturbances To Object Trajectoriesmentioning
confidence: 99%
“…Pursuer is shown moving laterally and forward in equal temporal intervals (t 1 -t 3 ) to intercept the target (helicopter). The vertical optical angle between the target and the horizon is α; the lateral angle between the target and pursuer is β McBeath, 2002;Shaffer et al, 2008); LOT, and OAC/GOAC have been shown to be consistent with the results of research on fielding ground balls in baseball (Sugar, McBeath, & Wang, 2006); SLOT and COV have been shown to be consistent with the results of research on dogs navigating to catch Frisbees (Marken, 2005;Shaffer et al, 2004); and LOT, OAC, and GOAC have been shown to be consistent with the results of research on robotic navigation for interception (Sugar & McBeath, 2001). …”
Section: Research Testing Object Interception Strategiesmentioning
confidence: 99%
“…However, LOT only couples the catcher's lateral movement to his movement toward the ball, for which he needs an additional strategy. Some experimental data appear to be consistent with LOT (Shaffer and McBeath 2002), but in other experiments the catcher's behavior would seem to preclude LOT as a general strategy (McLeod et al 2001). Another method to cope with the catcher's lateral movement was proposed by Tresilian (1995).…”
Section: Introductionmentioning
confidence: 86%